2012
DOI: 10.3168/jds.2011-4731
|View full text |Cite
|
Sign up to set email alerts
|

Alternative somatic cell count traits to improve mastitis resistance in Canadian Holsteins

Abstract: The objective of this study was to investigate whether alternative somatic cell count (SCC) traits are suitable as mastitis indicators in Canadian Holsteins. Mastitis data recorded by producers were available from the national dairy cattle health system in Canada. Mastitis was defined as a binary variable based on whether or not the cow had at least one mastitis case in the period from calving to 305 d after calving. The analyzed alternative SCC traits included mean somatic cell score (SCS) from different time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
48
6
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 11 publications
26
48
6
4
Order By: Relevance
“…In the current study, the onset time for mastitis 1 is in agreement with the results of several authors (1,8,10). The high frequency of cows affected by mastitis at the beginning of lactation may be explained by their high susceptibility due to the increased physiological demands after calving, and possibly to the pronounced sensitivity of the udder to infectious agents.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the current study, the onset time for mastitis 1 is in agreement with the results of several authors (1,8,10). The high frequency of cows affected by mastitis at the beginning of lactation may be explained by their high susceptibility due to the increased physiological demands after calving, and possibly to the pronounced sensitivity of the udder to infectious agents.…”
Section: Discussionsupporting
confidence: 80%
“…However, after 10 days of lactation, it was higher in multiparous cows than in heifers. Koeck et al (1) reported that the overall CM frequency -the percentage of cows with at least one case of CM in the period from 10 days prior to 241 days after first calving -was 10.1%. The increase in mastitis incidence with parity may be explained by physical changes in the udder and the permeability of teats' sphincter to pathogen agents.…”
Section: Discussionmentioning
confidence: 99%
“…Selection against clinical mastitis will likely leave cattle susceptible to infection with other mastitis pathogens, since bacteria require unique immune responses for host protection and mastitis pathogens have been demonstrated to change over time and geographically (2). Further, the heritability of mastitis resistance is low; it was recently demonstrated in Canadian Holsteins to be about 0.02 (40). Breeding for decreased SCS is an alternative, as it is genetically correlated with mastitis and has a higher heritability, of about 0.11 (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the heritability of mastitis resistance is low; it was recently demonstrated in Canadian Holsteins to be about 0.02 (40). Breeding for decreased SCS is an alternative, as it is genetically correlated with mastitis and has a higher heritability, of about 0.11 (40,41). However, SCS tends to useful for monitoring subclinical cases, and although decreasing bulk tank counts have been associated with a decline in subclinical mastitis, clinical mastitis continues to be a problem in many herds (24).…”
Section: Discussionmentioning
confidence: 99%
“…Rampino et al (2006) evaluated the SCC in uninfected mammary quarters in heifers during the first 24 days after birth, and found a geometric mean of 671 cells mL -1 at birth, decreasing to 47 mL -1 cells after 24 days. According to Koeck et al (2012), the threshold proposed by Canadian Holstein as mastitis indicator are 500,000 cells mL -1 from 5 to10 days of lactation. Schalm et al (1971) attributed the SCC in colostrum to excessive sloughing of epithelial cells in a small volume of milk in a gland that is restarting functional activity after a dormant period.…”
Section: Resultsmentioning
confidence: 99%